Therapeutic Applications of Magnetotactic Bacteria and Magnetosomes: A Review Emphasizing on the Cancer Treatment - Kotakadi, Sai Manogna; Borelli, Deva Prasad Raju; Nannepaga, John Sushma (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetotactic bacteria (MTB) are aquatic microorganisms have the ability to biomineralize magnetosomes, which are membrane-enclosed magnetic nanoparticles. Magnetosomes are organized in a chain inside the MTB, allowing them to align with and traverse along the Earth's magnetic field. Magnetosomes have several potential applications for targeted cancer therapy when isolated from the MTB, including magnetic hyperthermia, localized medication delivery, and tumour monitoring. Magnetosomes features and properties for various applications outperform manufactured magnetic nanoparticles in several ways. Similarly, the entire MTB can be regarded as prospective agents for cancer treatment, thanks to their flagella's ability to self-propel and the magnetosome chain's ability to guide them. MTBs are conceptualized as nanobiots that can be guided and manipulated by external magnetic fields and are driven to hypoxic areas, such as tumor sites, while retaining the therapeutic and imaging characteristics of isolated magnetosomes. Furthermore, unlike most bacteria now being studied in clinical trials for cancer treatment, MTB are not pathogenic but might be modified to deliver and express certain cytotoxic chemicals. This review will assess the current and prospects of this burgeoning research field and the major obstacles that must be overcome before MTB can be successfully used in clinical treatments.